SELF-ACTUALIZATION NEED IN MAJOR CHARACTER OF WATER FOR ELEPHANTS FILM - syarif Hidayat (STIBA IEC JAKARTA, 2019)
: This study analyzes a film entitled Water for Elephants directed by Francis Lawrence, written by Richard Lagravense. The research focuses on how does Jacob try to fulfill and satisfy his self-actualization need viewed from the Hierarchy of human needs of Abraham H. Maslow’s Theory? This film is carefully and accurately analyzed using the theory of hierarchy of human needs by Abraham H. Maslow. This research uses the qualitative method. The data are analyzed by watching, underlining, understanding, and identifying it. In this research, it find out that in fulfilling and satisfying his self-actualization need, Jacob has distractions from his lower-order needs. So, he must fulfill and satisfy them first to fulfill and satisfy his self-actualization need. In conclusion, he finally succeeds to fulfill and satisfy his self-actualization need by clearing the distractions from his lower-order needs which he fulfill and satisfy them first. Furthermore, people who cannot fulfill his basic needs can potentially do an evil thing.